2019
DOI: 10.1101/821389
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Screening of Tau Protein Kinase Inhibitors in a Tauopathy-relevant cell-based model of Tau Hyperphosphorylation and Oligomerization

Abstract: 26Tauopathies are a class of neurodegenerative disorders characterized by abnormal deposition of 27 post-translationally modified tau protein in the human brain. Tauopathies are associated with 28 Alzheimer's disease (AD), chronic traumatic encephalopathy (CTE), and other diseases. 29Hyperphosphorylation increases tau tendency to aggregate and forms neurofibrillary tangles 30 (NFT), a pathological hallmark of AD. In this study, okadaic acid (OA, 100 nM), a protein 31 phosphatase 1/2A inhibitor, was treated for… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 113 publications
(115 reference statements)
0
2
0
Order By: Relevance
“…20,21 In our subsequent study, we wanted to investigate the further mechanistic insights of the dmyc mediated rescue event and to identify a cellular connection between dmyc and tau protein. Since kinases are the major controller of the tau etiology 34 and shaggy (gsk3β) being one of the potent tau phosphorylating kinase, we performed a brief genetic screening study to examine any potential association between dmyc and shaggy in tau-mediated disease pathogenesis. Our initial studies indicated that shaggy emerges as a potential interactor that appeared to be working with dmyc in instigating rescue against tau toxicity.…”
Section: Cosuppression Of Dmyc With Shaggy Delivers Additive Rescue Against Taumediated Cellular Deficitsmentioning
confidence: 99%
“…20,21 In our subsequent study, we wanted to investigate the further mechanistic insights of the dmyc mediated rescue event and to identify a cellular connection between dmyc and tau protein. Since kinases are the major controller of the tau etiology 34 and shaggy (gsk3β) being one of the potent tau phosphorylating kinase, we performed a brief genetic screening study to examine any potential association between dmyc and shaggy in tau-mediated disease pathogenesis. Our initial studies indicated that shaggy emerges as a potential interactor that appeared to be working with dmyc in instigating rescue against tau toxicity.…”
Section: Cosuppression Of Dmyc With Shaggy Delivers Additive Rescue Against Taumediated Cellular Deficitsmentioning
confidence: 99%
“…All inhibitors showed strong effects toward the kinases investigated, with highlights on gsk-3β in nanomolar ranges [100]. Note that the tau protein has become an increasingly important target in drug discovery, contributing to the development of more efficient therapies for the AD treatment [101,102].…”
Section: Other Relevant Therapeutic Approaches In Ad Treatmentmentioning
confidence: 99%